TOURISM IN LOGISTICS: THE ROLE OF ROUTE TOURISM IN THE SUSTAINABLE DEVELOPMENT OF LOCAL ECONOMIES IN UZBEKISTAN (British Journal of Global Ecology and Sustainable Development, 2025)
Route tourism, which combines attractions into themed routes, is a strategic tool for stimulating economic development, especially in rural areas. This article analyzes the logistical aspects of route tourism, including planning, promotion, and institutional management, based on Lawrence's dissertation [4] and international case studies (Camino de Santiago, Queensland Heritage Trails, Hadrian's Wall). Particular attention is paid to the application of these principles in Uzbekistan, taking into account its unique cultural heritage and logistical challenges. A SWOT analysis is included to assess the potential and limitations of route tourism in Uzbekistan, and a logistical model for the sustainable development of routes is proposed. The results emphasize the importance of supply chain coordination, digital infrastructure, and stakeholder engagement to maximize economic benefits and ensure sustainability.